2022
DOI: 10.1039/d2qm00588c
|View full text |Cite
|
Sign up to set email alerts
|

High-entropy-alloy nanoparticles synthesized by laser metallurgy using a multivariate MOF

Abstract: We report the synthesis of multivariate MOFs with combinations of metal ions, including Mn2+, Fe3+, Co2+, Ni2+, Cu2+ and Zn2+. The permanent porosity and the evenly distributed metal components make...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…However, the laser conversion, metallurgy, manufacturing, annealing, scribing, or even ablation of hierarchical metal–organic materials like MOFs was started less than 4 years ago. , Nevertheless, these results are highly promising for photonics, electronics, and catalysis. Indeed, the laser conversion of MOFs makes it possible to obtain complex and even unique forms of nanomaterials such as metal oxides, , carbides and sulfides, multicomponent alloys, ,, carbon, and metal–carbon and organometallic nanostructures, ,, as well as to initiate the structural defects and laser writing. ,, Most of these works have been carried out in the nanosecond laser regime, paying special attention to the effect of the initial structure and composition of the MOF precursors , , and the laser power ,,,,, on the decomposition yield.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the laser conversion, metallurgy, manufacturing, annealing, scribing, or even ablation of hierarchical metal–organic materials like MOFs was started less than 4 years ago. , Nevertheless, these results are highly promising for photonics, electronics, and catalysis. Indeed, the laser conversion of MOFs makes it possible to obtain complex and even unique forms of nanomaterials such as metal oxides, , carbides and sulfides, multicomponent alloys, ,, carbon, and metal–carbon and organometallic nanostructures, ,, as well as to initiate the structural defects and laser writing. ,, Most of these works have been carried out in the nanosecond laser regime, paying special attention to the effect of the initial structure and composition of the MOF precursors , , and the laser power ,,,,, on the decomposition yield.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the laser conversion of MOFs makes it possible to obtain complex and even unique forms of nanomaterials such as metal oxides, 24,26 carbides 40 and sulfides, 41 multicomponent alloys, 28,31,42−44 carbon, 29 and metal−carbon and organometallic nanostructures, 30,32,45 as well as to initiate the structural defects 46 and laser writing. 25,27,47 Most of these works have been carried out in the nanosecond laser regime, paying special attention to the effect of the initial structure and composition of the MOF precursors [24][25][26][27][28][29][30][31][32][40][41][42][43][44][45]48 and the laser power 24,25,27,30,40,43 on the decomposition yield.…”
Section: Laser Conversionmentioning
confidence: 99%
“…There are fewer flaws in nanoparticles than in their bulk counterparts, and they have substantially better mechanical strength. However, some uses of nanomaterials may be negatively affected by their small size and high specific surface area, especially in applications for energy storage and conversion where nanomaterials have various benefits (Yan et al, 2022). The specific surface area, surface energy, and surface chemistry all play crucial roles in energy conversion and storage because these processes entail physical interaction and/or chemical reactions at the surface or interface.…”
Section: High Entropy Nanomaterialsmentioning
confidence: 99%
“…Subsequently, the group extended this basis to Multivariate metal-organic frameworks (MTV-MOFs). [92,93] Specifically, the group synthesized MOFs with different metal nodes and a single ligand in the same topology and used them as precursors to obtain nanoalloys by laser induction technology (Figure 7B-I).…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
“…Subsequently, Deng et al revealed that the metal oxide clusters present in CPM-70 exhibited excellent compatibility with transition metals such as Mn 2+ , Fe 3+ , Co 2+ , Ni 2+ , Cu 2+ , and Zn 2+ . [93] Leveraging this compatibility, they successfully prepared a series of MTV-MOFs containing one, two, three, and five different metals. Through laser-induced synthesis, the MTV-MOFs were transformed into metal nanoparticles, including high entropy alloy nanoparticles.…”
Section: Electrocatalysismentioning
confidence: 99%